Using Buddhist Principles in Social Media Consumption - Taileelas, Phra Kamolrat; Peykaeo, Phramaha Rangsey; Pandee, Phromphong (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 13 No 2 (2021): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This academic article aims to apply buddhist principles in social media consumption. Studies have shown that social media consumption It consists of two parts : (1) access to online media and (2) impact on accessing online media. At present, access to online media has a variety of purposes according to individual goals. Buddhist principles that can be used to help as a tool to pull the mindfulness of users to stop considering online media before using them are : the Kalama Sutta principle. Able to create a process of mindfulness to stop considering the media can be divided into 2 processes, namely 1) consuming buddhist online media and 2) knowing the value of buddhist online media. In order to use online media to be most effective for one's self, both initially having exposure until the use of those online media to be useful continued maximum success.